Implementasi Metode Geolocation Menggunakan Teknologi Webcam pada Sistem Absensi Pegawai - Muthmainnah, Ihmatull; Christanto, Febrian Wahyu; Manurung, Jonson; Sidiq, Maulana (Jurnal Sistem Informasi Galuh, 2024)
PT Omni Electrindo is a distributor of electrical components located at Jalan Sidodadi Timur No.22 Semarang still finds many problems in managing employee work absences. Attendance is still managed using Microsoft Excel and data is retrieved manually. At the beginning of 2020 there was an outbreak of the 2019 Coronavirus (Covid-19) which shook the world community, so the government issued a policy of limiting activities outside the home. In accordance with government policy, PT Omni Electrindo carries out work from home in turns. Based on this background, the researcher created an employee attendance system using geolocation and webcam methods in the HRIS application and using a prototype method which is expected to assist personnel in managing employee attendance data who work from home. In the system testing process, the results of the performance test were obtained with a score of B (74%) and resulted in a percentage of the results of the user questionnaire with 22% of respondents from a total of 60 employees at PT Omni, namely 91% of respondents choosing very good and 9% choosing good. Based on the test results obtained, the attendance recording process which previously took 20-30 minutes, now only takes 5 minutes. With this employee attendance system, it is expected to be able to assist the personnel and employees in the attendance process quickly and accurately.